2021
DOI: 10.3390/ani11082468
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-Pharmacodynamic Profile, Bioavailability, and Withdrawal Time of Tylosin Tartrate Following a Single Intramuscular Administration in Olive Flounder (Paralichthys olivaceus)

Abstract: The objective of this study was to demonstrate the pharmacokinetic–pharmacodynamic profile, bioavailability, and withdrawal time of tylosin tartrate (TT) administered to olive flounder via intramuscular (IM, 10 or 20 mg/kg, n = 240) and intravascular (IV, 10 mg/kg, n = 90) injections. Serum concentrations of tylosin were determined using a validated liquid chromatography-tandem mass spectrometry method. According to the non-compartmental analysis, the bioavailability of TT was 87%. After the IV injection, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Tylosin bioavailability following IM injection in chicken was ranged from 22.5 to 34.0%, while it was ranged from 70 to 95% in pigs, cows, and sheep after oral administration [ 12 14 ]. In contrast, the reported oral bioavailability in mink is poor (41%), while the IM-injected bioavailability in olive flounder is high (approximately 87%) [ 7 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tylosin bioavailability following IM injection in chicken was ranged from 22.5 to 34.0%, while it was ranged from 70 to 95% in pigs, cows, and sheep after oral administration [ 12 14 ]. In contrast, the reported oral bioavailability in mink is poor (41%), while the IM-injected bioavailability in olive flounder is high (approximately 87%) [ 7 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies suggested that tylosin-based antibiotics could be a good candidate to treat bacterial infections in fishes [ 1 , 7 ]. The pharmaco-kinetics/dynamics profiles of this drug have been explored to determine the optimal treatment regime in fishes [ 1 , 7 ]. Through a variety of studies on safety and efficacy of tylosin in fish, it was revealed that use of tylosin to fish has lots of advantages, including rapid absorption, low acute toxicity, and no critical adverse effects such as mortality or histopathological changes at appropriate therapeutic doses [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the current dose of 20 mg/kg may be insufficient for treating wild-type populations. While most studies ( Boothe et al, 2002 ; Avci and Elmas, 2014 ; Lee et al, 2021 ) have primarily focused on the drug concentrations in serum/plasma for PK/PD studies, it is crucial to consider the interstitial tissue as it is commonly invaded by most bacteria. Evaluating the antibiotic concentration in the interstitial fluid of the target tissue becomes essential for assessing the antibacterial effects ( Matzneller et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the aquaculture industry, antibiotics are commonly administered via injection for the olive flounder (Paralichthys olivaceus) owing to the advantages it offers over oral administration in certain circumstances [1,2]. Compared to other farmed fish species, the olive flounder has a calm demeanor and flat body, which makes physical injection of drugs feasible [1].…”
Section: Introductionmentioning
confidence: 99%